Key factors affecting composition and diversity of saproxylic beetle assemblages - Weiss, Matthias (Jihočeská univerzita, 2017)
The thesis concerns the community structure of saproxylic insects with a heavy focus on beetles. It presents a review on change of insect assemblages along small-to-large scale gradients and the importance of saproxylic organisms in forest ecosystems. The fine-scale vertical stratification of saproxylic beetles assemblages and their differences between forests habitats of different latitude and altitude are investigated. Further, the importance of open-grown trees for saproxylic diversity is assessed.
Key factors affecting composition and diversity of saproxylic beetle assemblages
Keywords: beetles; dead wood; temperate; tropical; forest; community; composition; stratification; horizontal; vertical; guilds; lowland; montane; czech republic; panama; beetles; dead wood; temperate; tropical; forest; community; composition; stratification; horizontal; vertical; guilds; lowland; montane; czech republic; panama